Electrical impedance tomography to measure lung ventilation distribution in healthy horses and horses with left‐sided cardiac volume overload - Muriel Sacks; David P. Byrne; Nicolas Herteman; Cristy Secombe; Andy Adler; Giselle Hosgood; Anthea L. Raisis; Martina Mosing (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Left‐sided cardiac volume overload (LCVO) can cause fluid accumulation in lung tissue changing the distribution of ventilation, which can be evaluated by electrical impedance tomography (EIT). Objectives To describe and compare EIT variables in horses with naturally occurring compensated and decompensated LCVO and compare them to a healthy cohort. Animals Fourteen adult horses, including university teaching horses and clinical cases (healthy: 8; LCVO: 4 compensated, 2 decompensated). Methods In this prospective cohort study, EIT was used in standing, unsedated horses and analyzed for conventional variables, ventilated right (VAR) and left (VAL) lung area, linear‐plane distribution variables (avg‐max VΔZLine, VΔZLine), global peak flows, inhomogeneity factor, and estimated tidal volume. Horses with decompensated LCVO were assessed before and after administration of furosemide. Variables for healthy and LCVO‐affected horses were compared using a Mann‐Whitney test or unpaired t‐test and observations from compensated and decompensated horses are reported. Results Compared to the healthy horses, the LCVO cohort had significantly less VAL (mean difference 3.02; 95% confidence interval .77‐5.2; P = .02), more VAR (−1.13; −2.18 to −.08; P = .04), smaller avg‐max VΔZLLine (2.54; 1.07‐4.00; P = .003) and VΔZLLine (median difference 5.40; 1.71‐9.09; P = .01). Observation of EIT alterations were reflected by clinical signs in horses with decompensated LCVO and after administration of furosemide. Conclusions and Clinical Importance EIT measurements of ventilation distribution showed less ventilation in the left lung of horses with LCVO and might be useful as an objective assessment of the ventilation effects of cardiogenic pulmonary disease in horses.